Absence of gamma interferon and interleukin 2 production during active visceral leishmaniasis. - Carvalho, E M (1985)
The lymphocytes from eight patients with active visceral leishmaniasis (VL), a disease associated with marked immunologic dysfunction, were examined for ability to produce interleukin 2 (IL-2) and gamma interferon during in vitro cultivation. It was found that both IL-2 and gamma interferon production, in response to leishmania antigen, was absent during the active disease, but was restored after successful chemotherapy. Untreated VL patients produced IL-2 and gamma interferon when stimulated with phytohemagglutinin (PHA). Six patients with either active cutaneous or mucosal leishmaniasis, a disease not associated with immunosuppression, showed high levels of gamma interferon in response to leishmania antigen and PHA. Since IL-2 and gamma interferon have been shown to have important roles in the immune response and in the killing of leishmania, their absence may represent a key defect in the immune response in VL.